Flexibility at the Core: What Determines Employment of Part-Time Faculty in Academia - Liu, Xiangmin; Zhang, Liang (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2013)
SummaryIn this study, we examine institutional predictors of part-time faculty employment in the higher education sector in the United States. We draw upon institutional and individual-level data to examine the variation in the intensity of part-time employment in faculty positions among a representative sample of higher education institutions. Institutional-level data are from Integrated Postsecondary Education Data System (IPEDS) and individual-level data are from National Study of Postsecondary Faculty (NSOPF). These data allow us to examine the impact of both economic factors and social environment on employment practices of colleges and universities. This analysis adds to the emerging literature on non-standard work arrangements in core organizational functions.Our results suggest that the employment of part-time faculty is significantly associated with a set of organizational attributes and characteristics such as institutional type, sources of revenue, and part-time student enrolment. Private institutions, on average, have higher levels of part-time faculty than their public counterparts. The proportion of part-time students and the share of institutional revenues derived from tuition and fees are positively associated with part-time faculty employment. Faculty unions are positively related to the employment of part-time faculty. Finally, institutions that have limited resource slack and pay high salaries to their full-time faculty members tend to employ a high proportion of part-time faculty. These results support the arguments that higher educational institutions actively design and adopt contingent work arrangements to manage their resource dependence with constituencies and to reduce labour costs.